Add to cart the impact of COVID-19 government stringency measures on e-commerce sales - Ma, Audrey Reiko S.; Villadolid, Leland Alfonso S.; Mendoza, Adrian R. (Quezon City School of Economics, University of the Philippines Diliman, 2023)
This paper investigates the effect of stringency on the growth of e-commerce sales in Australia, Canada, South Korea, the United States, and the United Kingdom at the height of the COVID-19 pandemic. We ran pooled ordinary least squares regressions using monthly data from March 2020 to December 2021, which covers the onset and the exponential rise of COVID-19 cases during the first two years of the pandemic. The results show that stringency has a lagged positive effect on e-commerce, indicating that stricter government containment measures encouraged more consumers and sellers to shift to e-commerce platforms at the height of the lockdowns. This is consistent with the technological acceptance framework which suggests that stringency increased the perceived usefulness of e-commerce since it provided a safe alternative that allowed consumers and firms to perform economic transactions without violating the government’s containment measures.
Thesis (BS Business Economics) - - University of the Philippines Diliman
Keywords: Electronic commerce -- Australia; COVID-19 (Disease) -- Economic aspects -- Australia; Electronic commerce -- Canada; COVID-19 (Disease) -- Economic aspects -- Canada; Electronic commerce -- Korea (South).; COVID-19 (Disease) -- Economic aspects -- Korea (South).; Electronic commerce -- United States; COVID-19 (Disease) -- Economic aspects -- United States; Electronic commerce -- United Kingdom; COVID-19 (Disease) -- Economic aspects -- United Kingdom